Gender Wage Gap and Commuting Time: An Empirical Analysis in The Jakarta Metropolitan Area - Abdillah, Thiraffi Akhsananta; Rini, Ariska Nurfajar; Alfianto, Okki (UI Scholars Hub, 2024)
This study aims to analyze the role of commuting time in explaining the gender wage gap in the Jakarta Metropolitan Area. This study presents an analysis of the gender wage gap as well as its explained and unexplained components using the Blinder-Oaxaca method with data provided by 2019 Jakarta Metropolitan Area Commuter Survey. The addition of commuting time as one of the explanatory factors is a novel aspect of the analysis. Two different methods known as ordinary least squares and the Heckman selection model are used to estimate wage equality for men and women. Depending on the methodology, estimates of the gap range from 3% to 11%. The decomposition of the gap reveals that between 2% and 3% of the gap is explained by the worker characteristic known as endowment factor while 7% to 12% of the gap is unexplained. This shows that the contribution of the unexplained factor to the income gap between genders is greater than the endowment factor. Commute time is found to account for 0,4% of the logarithmic wage gap explained by the worker characteristics. Results clearly identified that women have shorter average commute times compared to men, which may be due to women's willingness to be paid less as their compensating for shorter commute times.